Human capital criteria demanded by Takaful operators in Malaysia / Muhammad Azmi Othman - Othman, Muhammad Azmi (Faculty of Business and Management, 2011)
This research was conducted by focusing on the Human capital criteria demanded by Takaful operators in Malaysia. With the rapid growth of Takaful operations in Malaysia it bring the increase on demand for human capital in this industry and Takaful operators itself demanded for competence employees to work with them. The variables selected are experience, education level, and skill as a criteria demanded by Takaful operators.